P then Q. Logic, instantiation and norm: the importance of logic in the legal reasoning and the judicial practice (2019)
The purpose of these lines is to justify the importance of logic within of legal reasoning and judicial practice, understood as the one in which lawyers and judges operate. It is a reflection article, it is also an advance of the investigation entitled: minimum arguments of the judicial decision, and constitutes an analytical proposal, which starts from a contemporary problem, referring to logic and its practical utility. The proposal goes beyond the mere philosophical exercise and is aimed at litigating lawyers to show them how logic affects the elaboration of procedural forms such as demand.